Heat dissipation from a stationary brake disc, Part 1: Analytical modelling and experimental investigations. (May 2018) - Stevens, Kevin; Tirovic, Marko
The main aim of the research is to support the development of the commercial vehicle electric parking brake. Though nowadays widely used on passenger cars, electric parking brake applications on commercial vehicles present completely different challenges. With the brake mass, thermal capacity and required clamp forces an order of magnitude higher, safe parking demands much more attention. In the first instance, the priority is placed upon predicting heat dissipation from the brake disc only. The research is presented in two parts; part one (presented here) focuses on analytical modelling and experimental verification of predicted disc temperatures over long cooling periods, with part two investigating the air flow, velocities and convective heat transfer coefficients using computational fluid dynamics modelling, also followed by experimental validations. To begin the analytical analysis, a study was conducted into the variance in mean local convective heat transfer coefficients over a simplified brake disc friction surface, by investigating typical dimensionless air properties. A nonlinear equation was derived for the average surface convective heat transfer coefficient (h conv ) variability with temperature drop for the entire cooling phase. Starting from fundamental principles, first-order differential equations were developed to predict the bulk disc temperature. By including variation of the convective and radiative heat dissipation throughout the cooling period, a good correlation was achieved with measured values, to within 10%. Experiments were conducted on a specifically designed thermal rig which uses 15 kW induction heater to heat the disc. Numerous experiments proved the results are very repeatable, throughout the cooling period. It was established, for the grey cast iron brake disc with a fully oxidised surface, the emissivity value are practically constant at ɛ = 0.92. Although the research is being conducted on a brake disc, the results have generic application to any disc geometry, whatever the application.